International migration, poverty and care relations: the presence of immigrants in the city of Fortaleza, Ceará, Brazil - Iara Adeodato , Antônia; Maria Passos de Souza Bezerra , Leila (Seven Editora, 2023)
In this article we analyze the presence of immigrants in poverty in the city of Fortaleza, Ceará, Brazil. Driven to study the issue of immigration, poverty, assistance, margins and the state, we seek to transform the "problems of immigration" into sociological problems. The condition of immigrant in poverty gains complexity by bringing to the discussion the relationship of assistance and the foundations of the idea of citizenship. We start from the understanding that the very condition of "displaced" experienced by the immigrant, on the margins of the legal and illegal, implies interventions by the State. In this sense, we take with empirical field the relations of assistance experienced by immigrants in poverty who use the social assistance institutions of the capital of Ceará in search of social protection. Situated this proposal in the field of qualitative research, the research of ethnographic, bibliographic and documentary inspiration was used as methodological resources. In the research work, the analysis of journalistic articles was also used in order to verify the mechanisms of social classification of immigrants in poverty, their experiences and social representations. The production of research data pointed to new demands of contemporary transactional actors, migratory dynamics and urgent and current demands, which require the State a series of interventions, reaching Fortaleza as an important region of entry of international immigrants.